Brazilian state privatization and the funding of universities, science & technology in Bolsonaro’s government: A Privatização do Estado Brasileiro e o Financiamento das Universidades e da Ciência & Tecnologia no Governo Bolsonaro - Chaves, Vera Lucia Jacob; Guimarães, André Rodrigues; Reis, Luiz Fernando (Revista Brasileira de Política e Administração da Educação - Periódico científico editado pela ANPAE, 2022)
This study aims at analyzing Brazilian State privatization based on the Administrative Reform and the funding of Federal Universities and Science & Technology in Bolsonaro’s government. This documentary analysis is carried out with primary sources obtained from the Federal Chamber portal and the Integrated Planning and Budget System (IPBS). The results have suggested that the Administrative Reform, added to the Constitution Amendment 95, acts out on the State privatization by two main actions: reducing the funding of Federal Universities and Science and Technology and guaranteeing the profitability of financial capital with the payment of public debt. Este trabalho objetiva analisar a privatização do Estado brasileiro por meio da Reforma Administrativa e do financiamento das Universidades federais e da Ciência &Tecnologia no governo Bolsonaro. Trata-se de uma análise documental realizada com fontes primárias extraídas no portal da Câmara Federal. Os resultados indicam que a Reforma Administrativa, somada à EC 95, atuam na privatização do Estado por meio de duas grandes ações: reduzir o financiamento das Universidades federais e da Ciência e Tecnologia e garantir a rentabilidade do capital financeiro por meio do pagamento da dívida pública.